Critical care nutrition and COVID-19: a cause of malnutrition not to be underestimated. Issue 1 (27th May 2021) - Eden, Timothy; McAuliffe, Shane
Abstract : Malnutrition in critical care is highly prevalent and well documented to have adverse implications on morbidity and mortality. During the current COVID-19 pandemic, the evolving literature has been able to identify high risk groups in whom unfavourable outcomes are more common, for example, obesity, premorbid status, male sex, members from the Black, Asian and Minority Ethnic (BAME) community and others. Nutritional status and provision precritical and pericritical phase of COVID-19 illness is gaining traction in the literature assessing how this can influence the clinical course. It is therefore of importance to understand and address the challenges present in critical care nutrition and to identify and mitigate factors contributing to malnutrition specific to this patient group. We report a case of significant disease burden and the associated cachexia and evidence of malnutrition in a young 36-year-old male with Somalian heritage with no pre-existing medical conditions but presenting with severe COVID-19 during the first wave of the pandemic (March 2020). We highlight some key nutritional challenges during the critical phase of illness signposting to some of the management instigated to counter this. These considerations are hoped to provide further insight to help continue to evolve nutritional management when treating patients with COVID-19.